ANALISIS KELUHAN PASIEN TERKAIT PEMBUATAN AKUN MOBILE JKN SECARA ONLINE DI APLIKASI MOBILE JKN - Rahma Setyaning Putri; Enny Mar’atus Sholihah; Hermin Puji Astutik (Rena Cipta Mandiri, 2026)
The Mobile JKN application was developed to facilitate public access to healthcare services, including online account registration. However, patients still experience various obstacles during the account registration process, affecting the effectiveness of digital healthcare services. This study aimed to analyze patient complaints related to online Mobile JKN account registration, identify the contributing factors, and propose improvement strategies. This study employed a descriptive qualitative approach. Data were collected through observation and interviews with patients and healthcare staff involved in the Mobile JKN registration service. The problems were analyzed descriptively to identify the main causes of patient complaints. The results showed that the most common complaints included failure to verify personal data, one-time password (OTP) codes not being received, registered phone numbers or email addresses, application errors, unstable internet connections, and limited patient understanding of the registration procedure. These complaints were caused by system factors, technological limitations, and users' lack of knowledge regarding Mobile JKN registration Improvement efforts include enhancing system performance, providing clear registration guidelines, strengthening patient education, and improving coordination between healthcare facilities and BPJS Kesehatan. These efforts are expected to reduce patient complaints and improve the quality of digital healthcare services.